Analisis Respons Siswa Terhadap Model Guided Inquiry Berbasis Praktikum Pada Pembelajaran IPA Sub Materi Perpindahan Kalor - Mochammad Ricky Rifa'i (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The purpose of this study is to describe the analysis of student responses to the guided inquiry model based on practicum in science learning in the sub-material of heat transfer. The method used is quantitative with data collection including questionnaires. Data analysis techniques used in the form of percentage calculations and descriptive analysis. The results of the study explained that students' responses to the practical-based guided inquiry model in science learning the heat transfer sub-material got very positive and effective results. This is evidenced by the average percentage of student responses to the guided inquiry model of 87% with very effective criteria. This indicates that the syntax of the guided inquiry model has been done all by the teacher, the teacher's explanation is interesting at the beginning, so that it can increase student motivation and activity. Besides that, it is also related to practicum activities to get a percentage of 90% with very effective criteria. This indicates that students prefer practicum-based learning, because it can make students more active and easier to study the material because they are directly involved. Therefore, learning with a practicum-based guided inquiry model can be applied in learning.